Study of urinary 2-[2-(acetylamino-2-carboxyethyl]sulfanylbutanedioic acid, a mercapturic acid of rats treated with maleic acid. Issue 3 (5th August 2015) - Luo, Yu-Syuan; Tsai, Hsin-Yun; Chen, Hsin-Chang; Wu, Charlene; Shen, Li-Ching; Chung, Wen-Sheng; Chiang, Su-Yin; Wu, Kuen-Yuh
Graphical abstract: Highlights: MAMA was first synthesized, purified and characterized. A LC–MS/MS method was successfully developed for the analysis of MAMA. MAMA was present in rat urine after MA exposure and increased with dose. Urinary MAMA was validated to serve as a biomarker of current MA exposure in rats. Abstract: Maleic anhydride was reported illegally adulterated into starch to prepare traditional foods for decades in Taiwan. Maleic acid (MA), hydrolyzed from maleic anhydride, could cause kidney damages to animals. The potential health effects due to long-term MA exposures through food consumption have been of great concerns. Assessment of the dietary MA exposures could be very difficult and complicated. One of the alternatives is to analyze an MA-specific biomarker to assess the daily total MA intake. Therefore, this paper aimed to study the mercapturic acid of MA, 2-[2-(acetylamino)-2-carboxyethyl]sulfanylbutanedioic acid (MAMA), with our newly-developed isotope-dilution online solid-phase extraction liquid chromatography tandem mass spectrometry (ID-SPE-LC-MS/MS) method. MAMA was first synthesized, purified, and characterized with NMR to reveal two diastereomers and used for developing the analytical method. The method was validated to reveal excellent sensitivity with a LOD at 16.3 ng/mL and a LOQ at 20.6 ng/mL and used to analyze MAMA in urine samples collected from Sprague-Dawley rats treated with a single dose of 0 mg/kg, 6 mg/kg, and 60 mg/kg ( n = 5) of MA through gavage. Our results show dose-dependent increases in urinary MAMA contents, and 70% MAMA was excreted within 12 h with no gender differences ( p > 0.05). A half life of urinary MAMA was estimated at 6.8 h for rat. The formation of urinary MAMA validates it as a chemically-specific biomarker for current MA exposure. Future study of MA metabolism in vivo will elucidate mechanisms of MAMA formation, and analysis of this marker in epidemiology studies could help to shed light on the causal effects of MA on human.